PENGARUH PENGGUNAAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SD NEGERI 3 LEMBA KABUPATEN SOPPENG - Marwah; Muhammad Faisal; Latang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The quasi-experimental research with the nonequivalent control group design model is based on the low of critical thinking ability and learning outcomes of students of State Elementary School 3 Lemba Soppeng District. The study aims to to find out whether there is a significant influence of the use of Project Based Learning on the critical thinking skills and learning outcomes in the science and social learning of students in grade V State Elementary School 3 Lemba, Soppeng District. The sample consisted of 47 students, divided into 24 students in grade VA (without project based learning model) and 23 students in grade VB (with project based learning model). Techniques of data collection used are observation, tests, and documentation. The result showed that there was a significant influence of the use of the Project Based Learning model on the critical thinking skills and learning outcomes in social and science learning process of students in grade V State Elementary School 3 Lemba Soppeng District. The conclusion of this study is that the use of Project Based Learning has the impacts on improving critical thinking skills and learning outcomes in social and science learning process of students of grade V state elementary school 3 Lemba, Soppeng District.